Teori Behavioristik: Meninjau Penyebab Keterlambatan Belajar Membaca Menulis pada Siswa Sekolah Dasar - Komang Ayu Tantri Sastra Dewi; Ni Ketut Suarni; I Gede Margunayasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The ability to read and write is a basic ability that students must have in order to be able to receive and understand knowledge. Without reading, students will experience several obstacles in the learning process. The aim of this research is to find the causes of delays in reading and writing which are reviewed using behavioristic learning theory. The research carried out was descriptive qualitative research using a literature study method. The causes found were (1) lack of student response to learning to read; (2) lack of teacher role and stimulus in providing motivation; (3) lack of teaching materials provided using appropriate methods according to needs (4) lack of learning support or stimulus from the family. The solutions that can be provided are (1) accuracy in selecting and using media and learning methods; (2) invite parents to work together in providing support and training at home; (3) providing a stimulus to increase motivation in students as the key to successful learning. Therefore, with the existence of behavioristic learning theory which focuses on stimulus and response, we can find out the causes of delays in reading and writing because with this learning theory we can find out the causes and effects of every change in behavior.